Natriuresis During an Acute Intravenous Sodium Chloride Infusion in Conscious Sprague Dawley Rats Is Mediated by a Blood Pressure-Independent α1-Adrenoceptor-Mediated Mechanism - Frame, Alissa A.; Nist, Kayla M.; Kim, Kiyoung; Kuwabara, Jill T.; Wainford, Richard D. (Frontiers in Physiology, 2022)
The mechanisms that sense alterations in total body sodium to facilitate sodium homeostasis in response to an acute sodium challenge that does not increase blood pressure have not been fully elucidated. We hypothesized that the renal sympathetic nerves are critical to mediate natriuresis via alpha1 or Beta-adrenoceptors signal transduction pathways to maintain sodium balance in the face of acute increases in total body sodium content that do not activate the pressure-natriuresis mechanism. To address this hypothesis, we used acute bilateral renal denervation (RDNX), circumventricular organ ablation and alpha1 or beta adrenoceptor antagonism during an acute 1M NaCl sodium challenge in conscious male Sprague Dawley rats. During an acute 1M NaCl infusion, which does not produce a detectable change in mean arterial blood pressure, we observed profound natriuretic and sympathoinhibitory responses that were attenuated following acute RDNX (peak natriuresis microeq/min) sham 14.5+/-1.3 vs. acute RDNX: 9.2+/-1.4, p<0.05; plasma NE (nmol/L) sham control: 44+/-4 vs. sodium load 11+/-2, p<0.05; acute RDNX control: 42+/-6 vs. sodium load 25+/-3, p<0.05). In contrast circumventricular organ ablation by AV3V lesion did not impact the cardiovascular, renal excretory or sympathoinhibitory responses to an acute 1M NaCl infusion. Acute i.v. alpha1 adrenoceptor antagonism with terazosin evoked a significant drop in baseline blood pressure and significantly attenuated the natriuretic response to a 1M NaCl load (peak natriuresis (microeq/min) saline 17.2+/-1.4 vs. i.v. terazosin 7.8+/-2.5, p<0.05). In contrast, acute beta-adrenoceptor antagonism with i.v. propranolol infusion, did not impact the cardiovascular or renal excretory responses to an acute 1M NaCl infusion. Critically, the natriuretic response to an acute 1M NaCl infusion was significantly blunted in rats receiving a s.c. infusion of the alpha1-adrenoceptor antagonist terazosin at a dose that did not lower baseline blood pressure (peak natriuresis (microeq/min) sc saline: 18+/1 vs. sc terazosin 7+/-2, p<0.05). Additionally, a s.c. infusion of the alpha 1-adrenoceptor antagonist terazosin further attenuated the natriuretic response to a 1M NaCl infusion in acutely RDNX animals. Collectively these data indicate a specific role of a blood pressure-independent renal sympathetic nerve-dependent alpha 1-adrenoceptor-mediated pathway in the natriuretic and sympathoinhibitory responses evoked by acute increased total body sodium.